Impact of A Political Event on Stock Market: The 2024 Presidential Election Quick Count Version (Study on Indonesia Composite Index and LQ45 Stocks) - Jaya, Jessica Anna Mulia; Kurniasari, Widuri (Journal of Management and Business Review, 2026)
This study examines the capital market reaction to the announcement of the 2024 Election quick count results. Specifically, it analyzes the differences in Abnormal Returns of LQ45 stocks and the Market Cumulative Abnormal Returns before and after the announcement. This research employs a quantitative study approach using secondary data from companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX). The observation period covers five days before and five days after the quick count announcement of the 2024 Presidential Election. The sample consists of 45 companies included in the LQ45 index. Data analysis was conducted using descriptive statistics, normality tests, and the paired sample t-test to compare market reactions before and after the event. The findings indicate that the market showed a positive response to the quick count announcement, reflected in the difference in the Market Cumulative Abnormal Returns. However, there was no significant difference in the Abnormal Returns of individual LQ45 stocks. These results suggest that political events may influence overall market sentiment without necessarily affecting individual stock returns. Future research is recommended to extend the observation period, include other stock indices, and examine additional political or macroeconomic events to provide broader insights into market reactions